A Prospective Study of Predictors for Post Laparotomy Abdominal Wound Dehiscence - Garg Ramneesh (Journal of Clinical and Diagnostic Research, 2014)
Introduction: Break in continuity of the skin with or without deeper tissues, following laparotomy, results in abdominal wound dehiscence. This study was done to evaluate the risk factors that lead to wound dehiscence in post-operative period. Material and Methods: This was a prospective study done on 50 patients who developed wound dehiscence (partial or complete) following laparotomy. The pre-operative investigations, intraoperative findings and any post-operative complications were recorded in a specified Performa. Results: The highest incidence of wound dehiscence was found to be in patients of fourth decade, with male preponderance. 16 patients were found to be obese (BMI>30) and 13 patients were anemic. Twelve had low serum albumin, 16% had raised serum bilirubin while 4 patients were diabetics. Renal failure was found in 19 of 50 patients. 92% patients were with ASA score I E. In 88% of patients, laparotomy wounds were either contaminated or dirty. Post-operative nausea and vomiting was found in 10 patients and cough in 9 patients. Conclusions: Abdominal wound dehiscence after laparotomy is a surgical emergency with high morbidity and mortality leading to escalation in hospital costs and prolonged illness. This complication can be avoided if the factors involved in wound dehiscence are properly addressed.